Hydrogenation of Sulfoxides to Sulfides under Mild Conditions Using Ruthenium Nanoparticle Catalysts1. Issue 32 (20th June 2014) - Mitsudome, Takato; Takahashi, Yusuke; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract The first demonstration of the hydrogenation of sulfoxides under atmospheric H2 pressure is reported. The highly efficient reaction is facilitated by a heterogeneous Ru nanoparticle catalyst. The mild reaction conditions enable the selective hydrogenation of a wide range of functionalized sulfoxides to the corresponding sulfides. The high redox ability of RuOx nanoparticles plays a key role in the hydrogenation.